Etude de la croissance chez L’oursin de mer Paracentrotus Lividus (Lamarck, 1816). - Bendris Chaima; Hocine Amel (My University, 2022)
Our work was carried out on the east coast of Algeria, on the shores of the city of El Kala. The sampling of 335 individuals at two stations was carried out from April 2021 until July 2021. The follow-up of the size structure made it possible to report the arrival of young recruits during the months of April, May and June with a minimum size of 26 mm. The study of the condition index shows two peaks in body weight, the first in the middle of spring (2.04% in April). A second peak very similar to the first is recorded at the end of the spring season at the beginning of summer (3.09% in June). The calculation of the relation between the height and the weight in the sea urchin shows a proportionality in the linear and weight growth, expressed by a high correlation coefficient which varies between (R = 0.68 May Station 1 and 0, 91 April Station 1). The study of the allometry coefficient ''a'' is less than 3, and which goes from 0.92 in June Station 1 to 2.73 recorded in May at the level of station 1, thus reflecting a growth in allometry lowering. ------------------------------------------------------------------------------------------------------------------------------------------------- تم انجاز عملنا على الساحل الشرقي للجزائر على ضفاف مدينة القالة. تم أخذ عينات من 335 فردًا في محطتين من أفريل 2021 حتى جويلية 2021. أتاحت متابعة هيكل الحجم الإطلاع علي وجود قنافذ ذات حجم صغير حيث توافدت خلال أشهر أفريل ومايو وجوان بحجم لا يقل عن 26 ملم. تظهر دراسة مؤشر الحالة ذروتين في وزن الجسم، الأولى في منتصف الربيع (2.04٪ في أفريل) بحيث تم تسجيل ذروة ثانية مشابهة جدًا للذروة الأولى في نهاية موسم الربيع في بداية الصيف (3.09٪ في جويلية). يظهر حساب العلاقة بين الارتفاع والوزن في قنفذ البحر التناسب في النمو الخطي والوزن، معبرًا عنه بمعامل ارتباط مرتفع يتراوح بين (R = 0.68 May Station 1 and 0، 91 April Station 1). دراسة معامل التباين" '' a '' أقل من3، والتي تتراوح من 0.92 في محطة يونيو 1 إلى 2.73 المسجلة في مايو على مستوى المحطة 1، مما يعكس نموًا في انخفاض قياس التباين. --------------------------------------------------------------------------------------------------------------------------------------------------- Notre travail a été réalisé au niveau de la cote est algérienne, sur les rive de la ville d’El Kala. L’échantillonnage 335 individus sur deux stations a été effectué de d’Avril 2021 jusqu'à juillet 2021. Le suivie des structure des tailles a permis de signalé l’arrivé des jeunes recrus pendant le mois d’avril, Mai et juin avec une taille minimale de 26 mm. L’étude de d’indice de condition, permet de constater deux pics du poids corporel le premier en pleine période printanière (2,04% en Avril). Un second pic très similaire au premier est enregistré à la fin de la saison printanière début d'été (3,09% en juin). Le calcule de la relation entre la taille et le poids chez l'oursin de mer montre une proportionnalité dans la croissance linéaire et pondérale, exprimée par un de coefficient de corrélation élevé qui varie entre (R = 0,68 Mai Station 1 et 0,91 Avril Station 1). L’étude du coefficient d’allométrie ‘’a ’’ est inférieur à 3, et qui passe de 0,92 en Juin Station 1 à 2,73 enregistré en Mai au niveau de la station 1, traduisant ainsi une croissance d’allométrie minorante.